2015
DOI: 10.15407/fz62.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of proliferation related transcription factor genes in U87 glioma cells with IRE1 knockdown: upon glucose and glutamine deprivation

Abstract: Glycolysis and glutaminolysis as well as endoplasmic reticulum stress are required for tumor progression suggests through regulation of the cell cycle. Inhibition of ERN1/IRE1 (endoplasmic reticulum to nucleus signaling 1/inositol requiring enzyme 1), a central mediator of endoplasmic reticulum stress, significantly suppresses glioma cell proliferation and tumor growth as well as modifies sensitivity gene expressions to glucose and glutamine deprivation. We have studied the expression of genes encoded transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…Previously was shown that glutamine withdrawal affected the expression of several tumor growth related genes and that the effect of glutamine deprivation on most of these genes expression is dependent on ERN1 signaling enzyme function [19][20][21][22][23]. However, the regulation of the expression of many other tumor growth related genes by glutamine deprivation in relation to inhibition of ERN1 to not to be clarified yet.…”
Section: The Expression Of a Subset Of Genes Encoding Important Tumormentioning
confidence: 99%
“…Previously was shown that glutamine withdrawal affected the expression of several tumor growth related genes and that the effect of glutamine deprivation on most of these genes expression is dependent on ERN1 signaling enzyme function [19][20][21][22][23]. However, the regulation of the expression of many other tumor growth related genes by glutamine deprivation in relation to inhibition of ERN1 to not to be clarified yet.…”
Section: The Expression Of a Subset Of Genes Encoding Important Tumormentioning
confidence: 99%
“…Glutamine, as a substrate for glycolysis, is an important for the development and a more aggressive behavior of gliomas, which are highly aggressive tumors with very poor prognosis (Colombo et al 2011;Yalcin et al 2014;Zhao et al 2017;Alimohammadi et al 2020). Glutamine supply and endoplasmic reticulum stress are very important and complementary factors for the tumor growth and inhibition of ERN1/IRE1 (endoplasmic reticulum to nucleus signaling 1/inositol requiring enzyme 1) mediated stress signaling can significantly modify the effects of glutamine deprivation on some gene expressions (Minchenko et al 2013(Minchenko et al , 2015a(Minchenko et al , 2021Tsymbal et al 2016). It has been shown that ERN1 -XBP1 pathway is also essential for the glucose response and protection of β cells (Riabovol et al 2019).…”
mentioning
confidence: 99%
“…Transcription factors play an important role in malignant tumor growth preferentially through ERN1 (endoplasmic reticulum to nucleus signaling 1) signaling pathway of endoplasmic reticulum stress (Minchenko et al 2015b(Minchenko et al , 2015cTsymbal et al 2016). The homeobox proteins represent an important group of transcription factors, which are related to tumorigenesis and are largely investigated (Guca et al 2018;Le Magnen et al 2018;Miyashita et al 2018;Hamaidi et al 2019;Li et al 2019).…”
mentioning
confidence: 99%
“…After WGCNA and protein–protein interaction (PPI) analysis, general transcription factor IIF polypeptide 2 ( GTF2F2 ) was identified as the hub gene. GTF2F2 combines with general transcription factor IIF polypeptide 1 (GTF2F1) to form a heteromeric general transcription initiation factor (TFIIF), which subsequently binds to DNA-dependent RNA polymerase II ( Sasaki et al, 2013 ; Tsymbal et al, 2016 ). RNA polymerase II plays a critical role in mRNA synthesis, and GTF2F2 is essential for the initiation and elongation phases of gene transcription ( Sasaki et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%